Core Practices for Teaching English Pronunciation in Post-Pandemic Contexts at Tertiary Level [Prácticas Basales Para Enseñar Pronunciación del Inglés en Contextos Terciarios de Posvirtualidad] - Cid-Uribe, M (Eagora Science, 2022)
The teaching of English pronunciation in a pandemic context at tertiary level was characterized by the absence of face to face student/teacher interaction; although this interaction fosters the learning and improves oral proficiency in a foreign language, the conditions of pandemic affected the teaching-learning process and diminished the speed of internalization of English pronunciation. It is hypothesized that the use of core practices for pronunciation teaching will improve oral competence. The results of this research show that a period of constant, continuous, and measurable formal instruction using core practices will allow the access to the expected oral competence. © GKA Ediciones, authors.